2019
DOI: 10.1534/g3.119.400552
|View full text |Cite
|
Sign up to set email alerts
|

Genomics Analysis of L-DOPA Exposure inDrosophila sechellia

Abstract: Drosophila sechellia is a dietary specialist fruit fly that evolved from a generalist ancestor to specialize on the toxic fruit of Morinda citrifolia. This species pair has been the subject of numerous studies where the goal has largely been to determine the genetic basis of adaptations associated with host specialization. Because one of the most striking features of M. citrifolia fruit is the production of toxic volatile compounds that kill insects, most genomic studies in D. sechellia to date have focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…Previous studies examining gene expression responses in D. sechellia to the volatile fatty acids in noni fruit have focused on examining all of the differentially expressed genes in response to either OA or HA treatment to identify genes involved in evolved toxin resistance (Lanno et al 2017, Lanno et al 2019a, Drum et al In Review (BIORXIV/2021). Interestingly, only 19.7% and 28.9% of DEGs found in these studies are responding to specifically to OA or HA treatment respectively, and only two genes are found that respond to both OA and HA treatment but no other treatments.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies examining gene expression responses in D. sechellia to the volatile fatty acids in noni fruit have focused on examining all of the differentially expressed genes in response to either OA or HA treatment to identify genes involved in evolved toxin resistance (Lanno et al 2017, Lanno et al 2019a, Drum et al In Review (BIORXIV/2021). Interestingly, only 19.7% and 28.9% of DEGs found in these studies are responding to specifically to OA or HA treatment respectively, and only two genes are found that respond to both OA and HA treatment but no other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Osi6 and several other Osiris genes are significantly increased in D. sechellia in response to OA (Lanno et al 2017), and Osi6 is one of the 25 DEGs found only in OA and not in response to any of the other noni components. However, esterase 6 (Est-6) RNAi has been previously shown to alter survival in D. melanogaster exposed to OA and the activity of esterase enzymes has previously been shown to be involved in OA resistance (Lanno et al 2017, Lanno et al 2019a, Lanno et al 2019b. Interestingly, Est-6 expression is significantly enriched in response to L-DOPA and noni treatments, but not upon OA or HA exposure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations